Bifunctional Asymmetric Fabric with Tailored Thermal Conduction and Radiation for Personal Cooling and Warming. (March 2022) - Peng, Yucan; Lee, Hiang Kwee; Wu, David S.; Cui, Yi
Abstract: Personal thermal management is emerging as a promising strategy to provide thermal comfort for the human body while conserving energy. By improving control over the heat dissipating from the human body, personal thermal management can provide effective personal cooling and warming. Here, we propose a facile surface modification approach to tailor the thermal conduction and radiation properties based on commercially available fabrics, to realize better management of the whole heat transport pathway from the human body to the ambient. A bifunctional asymmetric fabric (BAF) offering both a cooling and a warming effect is demonstrated. Due to the advantages of roughness asymmetry and surface modification, the BAF demonstrates an effective cooling effect through enhanced heat conduction and radiation in the cooling mode; in the warming mode, heat dissipation along both routes is reduced for personal warming. As a result, a 4.6 °C skin temperature difference is measured between the cooling and warming BAF modes, indicating that the thermal comfort zone of the human body can be enlarged with one piece of BAF clothing. We expect this work to present new insights for the design of personal thermal management textiles as well as a novel solution for the facile modification of available fabrics for both personal cooling and warming.